Lingual Leishmaniasis Presenting to Maxillofacial Surgery in UK with Successful Treatment with Miltefosine. (30th September 2013) - Kassam, K.; Davidson, R.; Tadrous, P. J.; Kumar, M.
Abstract : Leishmaniasis is a disease that is caused by protozoa of the genus Leishmania, which is prevalent in tropical and subtropical areas. Clinical forms of leishmaniasis are particularly diverse representing a complex of diseases. We present a case of lingual Leishmaniasis in an immunocompetent man. The lesions were caused by Leishmania donovani/infantum species. The patient responded excellently to miltefosine treatment, with no reactivation during followup. To the authors' knowledge, it is the first such case of successful miltefosine treatment in this unusual variant of leishmaniasis occurring on the tongue.